THE PRACTICAL WAYS FOR IMPROVING LISTENING COMPREHENSION IN ENGLISH - Oblaqulova Dinora Jamshid qizi; Ibragimov Nuriddin Talibovich (Research Focus International Scientific Journal, 2023)
This article deals with numerous reasonable and practical ways of boosting listening skills in the English language. Also, all suggested methods and solutions are based on reliable facts and details. They will be supported with solid reasons as well as examples.